2014
DOI: 10.1007/s00167-014-3212-1
|View full text |Cite
|
Sign up to set email alerts
|

Recovery in knee range of motion reaches a plateau by 12 months after total knee arthroplasty

Abstract: Prospective case series, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 21 publications
0
34
2
Order By: Relevance
“…Fourthly, the correlation between the variability of the intraoperative values and postoperative extension angles was analyzed at the one-year follow-up, as further changes may occur with longer followup periods. Previous longitudinal studies have reported that the ROM and clinical outcomes reach a plateau with few clinically significant changes at the one-year follow-up; however, in future studies, longer follow-up periods should be considered [20,22]. Fifth, we described the effect of intraoperative extension gap on postoperative flexion contractures in detail.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Fourthly, the correlation between the variability of the intraoperative values and postoperative extension angles was analyzed at the one-year follow-up, as further changes may occur with longer followup periods. Previous longitudinal studies have reported that the ROM and clinical outcomes reach a plateau with few clinically significant changes at the one-year follow-up; however, in future studies, longer follow-up periods should be considered [20,22]. Fifth, we described the effect of intraoperative extension gap on postoperative flexion contractures in detail.…”
Section: Discussionmentioning
confidence: 92%
“…The range of motion (ROM) after total knee arthroplasty (TKA) plays an important role in postoperative knee function [17,18,22]. Flexion contractures after TKA are common and are caused by a response to pain and effusion [5].…”
Section: Introductionmentioning
confidence: 99%
“…One limitation of this study was that patients were only followed up for 24 months. Based on literature that functional scores would plateau after 12 months, 29 insignificant differences are expected with longer follow-ups. Nevertheless, the authors will continue monitoring the functional outcomes of the patients enrolled in this study for 10 years postoperatively.…”
Section: Discussionmentioning
confidence: 95%
“…The conservative therapy included physiotherapy according to published protocol [10] employing drop and dangle technique [11]. Patients who remained symptomatic after six weeks of rehabilitation underwent repeat courses up to 12 months post op when improvement has been shown to reach a plateau [12].…”
Section: Inclusion/exclusion Criteriamentioning
confidence: 99%